Monetary policy - Fisher, Douglas (London : Macmillan, 1976)
This book takes a broad view of monetary policy, which is seen as depending on fiscal and balance-of-payments policy, as well as on the skills and perception of the monetary authorities. It considers the problems affecting Macroeconomic policy as a result of poor data, inadequate models etc. Also it examines some international aspect of domestic monetary policy with reference to U.S and U.K.
includes bibliography pp. 83-91
usc 05/07/17
Loans
Keywords: Monetary policy